Hepatocyte-targeted expression by integrase-defective lentiviral vectors induces antigen-specific tolerance in mice with low genotoxic risk - Mátrai, Janka; Cantore, Alessio; Bartholomae, Cynthia C.; Annoni, Andrea; Wang, Wei; Acosta-Sanchez, Abel; Samara-Kuko, Ermira; De Waele, Liesbeth; Ma, Ling; Genovese, Pietro; Damo, Martina; Arens, Anne; et al. (Hepatology, 2011)
Lentiviral vectors are attractive tools for liver-directed gene therapy because of their capacity for stable gene expression and the lack of preexisting immunity in most human subjects. However, the use of integrating vectors may raise some concerns about the potential risk of insertional mutagenesis. Here we investigated liver gene transfer by integrase-defective lentiviral vectors (IDLVs) containing an inactivating mutation in the integrase (D64V). Hepatocyte-targeted expression using IDLVs resulted in the sustained and robust induction of immune tolerance to both intracellular and secreted proteins, despite the reduced transgene expression levels in comparison with their integrase-competent vector counterparts. IDLV-mediated and hepatocyte-targeted coagulation factor IX (FIX) expression prevented the induction of neutralizing antibodies to FIX even after antigen rechallenge in hemophilia B mice and accounted for relatively prolonged therapeutic FIX expression levels. Upon the delivery of intracellular model antigens, hepatocyte-targeted IDLVs induced transgene-specific regulatory T cells that contributed to the observed immune tolerance. Deep sequencing of IDLV-transduced livers showed only rare genomic integrations that had no preference for gene coding regions and occurred mostly by a mechanism inconsistent with residual integrase activity. Conclusion: IDLVs provide an attractive platform for the tolerogenic expression of intracellular or secreted proteins in the liver with a substantially reduced risk of insertional mutagenesis.